ANALISIS PERISTIWA KEGAGALAN PADA ”LEAF SPRING” TRUK COLT DIESEL PENGANGKUT PASIR - Sepfitrah -; Yose Rizal (Universitas Pasir Pengaraian, 2013)
Vehicle for pengakut goods such as trucks, have tended to point loading up backward toward the center of the body. The back of the truck so the suspension will experience a greater deflection than the suspension on the front. Truck rear suspension system uses leaf springs, which will undergo the toughest conditions in the compressive load over and over again, so the potential for failure due to material fatigue limit passing.In this research investigation into the leaf springs on trucks carrying sand in the form of a broken failure. A broken spring release of a series of truck suspension system to cut the rupture area and certain areas that want to be observed as a test specimen.